2016
DOI: 10.1038/srep22086
|View full text |Cite|
|
Sign up to set email alerts
|

8-Oxoguanine accumulation in mitochondrial DNA causes mitochondrial dysfunction and impairs neuritogenesis in cultured adult mouse cortical neurons under oxidative conditions

Abstract: Oxidative stress and mitochondrial dysfunction are implicated in aging-related neurodegenerative disorders. 8-Oxoguanine (8-oxoG), a common oxidised base lesion, is often highly accumulated in brains from patients with neurodegenerative disorders. MTH1 hydrolyses 8-oxo-2′-deoxyguanosine triphosphate (8-oxo-dGTP) to 8-oxo-dGMP and pyrophosphate in nucleotide pools, while OGG1 excises 8-oxoG paired with cytosine in DNA, thereby minimising the accumulation of 8-oxoG in DNA. Mth1/Ogg1-double knockout (TO-DKO) mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 42 publications
1
57
0
2
Order By: Relevance
“…Many studies have shown the role of mitochondria on neuritogenesis through calcium handling and ATP production4344. Recently, we demonstrated that 8-oxoG accumulation in neuronal mtDNA results in mitochondrial dysfunction, and leads to poor neurite outgrowth with decreased complexity of neuritic arborization, using isolated cortical neurons from mice lacking both 8-oxo-dGTP-depleting MTH1 and 8-oxoG excising OGG130, similar to the AD model neurons. In the present study, we showed that rhTFAM efficiently suppresses mitochondrial dysfunction accompanied by reduced accumulation of 8-oxoG and single strand breaks in mtDNA (Fig.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Many studies have shown the role of mitochondria on neuritogenesis through calcium handling and ATP production4344. Recently, we demonstrated that 8-oxoG accumulation in neuronal mtDNA results in mitochondrial dysfunction, and leads to poor neurite outgrowth with decreased complexity of neuritic arborization, using isolated cortical neurons from mice lacking both 8-oxo-dGTP-depleting MTH1 and 8-oxoG excising OGG130, similar to the AD model neurons. In the present study, we showed that rhTFAM efficiently suppresses mitochondrial dysfunction accompanied by reduced accumulation of 8-oxoG and single strand breaks in mtDNA (Fig.…”
Section: Discussionmentioning
confidence: 76%
“…It is noteworthy that not only ROS production but also intracellular Aβ accumulation is significantly suppressed by hTFAM, probably through increased expression of transthyretin which is known to suppress Aβ aggregation26. Moreover, poor neuritogenesis found in the iPSC-derived AD neuron model which is also likely to be a consequence of mitochondrial dysfunction30, is also efficiently improved by hTFAM (Figs 5a and 7d,e). Inhibition of transthyretin mRNA expression by phenylalanine abolished the improvement in neuritogenesis with a significantly reduced level of transthyretin (Figs 6e and 7f), which is likely to be associated with hTFAM in mitochondria (Fig.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Sheng et al demonstrated that 3-NP exposure induces nuclear DNA oxidation and PARP activation in striatal microglia; it also induces mitochondrial DNA oxidation and calpain activation in medium spiny neurons (23), whereas isolated neurons from MTH1/OGG1 double-deficient mice accumulated 8-oxoG only in mitochondrial DNA, and the mice thus underwent impaired neuritogenesis in vitro (42). Consistent with these findings, our present in vitro and in vivo experiments showed that nuclear DNA oxidation in microglia is associated with PARP activation, which was reversed by MUTYH deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various types of oxidative lesions, 8-oxoguanine (8-oxoG) is one of the major oxidized base in both nucleotide pools and polymerized DNA, which is strongly mutagenic as it can mispair with adenine residues instead of the cysteine residues, leading to GC to AT transversion mutations (Leon et al, 2016). 8-oxoG-DNA glycosylase (OGG1) excises 8-oxoG paired with cytosine in DNA, and 8-oxoG nucleoside triphosphatase (MTH1) hydrolyzes 8-oxo-dGTP in nucleotide pools, avoid incorporation of 8-oxo-dGMP into DNA, thus preventing the accumulation of oxidative DNA damage (Sheng et al, 2012).…”
Section: Introductionmentioning
confidence: 99%